PERAN BRAND TRUST DALAM MEMEDIASI BRAND EXPERIENCE, BRAND PERSONALITY DAN BRAND COMMUNITY TERHADAP BRAND LOYALTY - Alifah Ratnawati; Annisa Ayu Lestari (Jurnal Ekonomi dan Bisnis, 2018)
This study aims to know and analyze the influence of brand experience, brand personalityand brand community to brand loyalty with brand trust as a variable intervening on Oriflameproducts .. The population is the consumer who ever bought the product Oriflame in Semarang,with the number of samples of 100 respondents. The sampling technique used in this researchis convenience sampling or convenience .. The analysis tool is path analysis, where previouslytested the validity and reliability as well as the classical assumption test.Test results show thatbrand experience, brand personality and brand personality proved to have a significant positiveeffect on brand trust and brand loyalty. Brand trusts have a positive influence on brand loyalty.Brand trust can be an intervening variable between brand experience and brand personalitytoward brand loyalty. Brand trust can be an intervening variable between brand communitytowards repurchase meaning higher brand community, the more consumers can strengthenthe understanding of its members due to high trust to Oriflame brand, so that will increasinglyincrease customer loyalty to the brand.Keywords: Brand experience, brand personality, brand community, brand trust brand loyalty